INFORMATIVE OF EXPERIMENTAL ACOUSTIC EMISSION SIGNALS PARAMETERS IN TECHNOLOGICAL PROCESSES MACHINING COMPOSITE - Filonenko, Sergii; Zaritskyi, Oleg (Proceedings of National Aviation University (archive), 2018)
Purpose: The aim of this article is the experimental study of machining composite speed effect on the acoustic emission energy parameters. Methods: The studies were based on the recording and processing of experimental acoustic emission signals during the composite material machining. The statistical processing of experimental acoustic emission signals with an analysis of the acoustic radiation energy parameters was made. The analysis of acoustic emission statistical energy parameters regularities change and their sensitivity to machining composite speed changes was made, as well as a comparison sensitivity of acoustic radiation energy and amplitude parameters. Results: Is obtained, that at composite machining speed ascending there is increasing of experimental acoustic emission signals energy average level and value of its spread. Thus the greatest increasing is watched in acoustic radiation energy average level dispersion. Is determined, that the experimental acoustic emission signals statistical energy parameters have not linear nature of ascending. The ascending of experimental acoustic emission signals energy parameters advances ascending their amplitude parameters. Discussion: The experimental researches of acoustic radiation energy parameters at ascending of composite machining speed are conducted. The statistical data processing has shown, that a regularity of acoustic radiation signal energy average level ascending, its standard deviation and the dispersions are well described by exponential functions. Thus is shown, that the greatest sensitivity to ascending of composite machining speed there is the experimental acoustic emission signals energy average level dispersion. A comparison of acoustic emission amplitude and energy parameters has shown, that the percentage increment of experimental signals energy average level dispersion advances a percentage increment of energy average level and its standard deviation, and as increment of all acoustic radiation statistical amplitude parameters The outcomes of the conducted researches can be used at the decision some problems: optimization of machining process parameters; development of methods verification, monitoring and control the technological processes parameters.